Formulation of Watermelon Rind (Citrullus vulgaris schard) and Secang (Caesalpinia sappan L.) Jam as Functional Food Rich in Antioxidants - Aziz, Rahmawati; Jumrah, Elfira; Agustina, Ayu Safitri; Abubakar, Andi Nur Fitriani; Zulkarnain, A. Mutiara (Indonesian Journal of Chemical Research, 2023)
The body's immune system is one of the natural defenses in the human body, functioning to ward off various diseases, including those that emerged after the Covid-19 pandemic. One plant with potential as an antioxidant and easily found in the environment is watermelon. Jam made from watermelon rind and secang wood, with various formulations, namely 100% watermelon rind: 0% secang (F1), 90% watermelon rind: 10% secang (F2), 80% watermelon rind: 2% secang (F3), and 70% watermelon rind: 3% secang (F4), is expected to possess good antioxidant properties. A promising antioxidant formulation for watermelon rind jam and secang is the one with 70% watermelon rind and 30% secang (F4), having an IC50 value of 144.27 g/mL, which is classified as a moderate antioxidant. Among the four jam formulations, panelists preferred the jam formulation (F4) without the addition of sweetened condensed milk in terms of color and texture. However, for the jam formulation (F4) with the addition of sweetened condensed milk, panelists favored it in terms of aroma and taste. The jam formulation (F4) meets the quality standards for fruit jam based on INS 3746:2008, including total plate count, arsenic, and tin categories.